A study on Socio –Economic Status of the Tribal Women in B.R. Hills, Karnataka. - Prof. P. Jayashree, Dr.Ramya. R, and Nalina.H.P (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
B.R. Hills is located in the southeast of Karnataka. The hill station is named for the Hindu God Ranganathaswamy. It mainly comes under the Western edge of the Western ghats. B.R. hills is a pilgrim site, famous for Ranganathaswamy Temple. Many festivals and Hindu rituals occur in this place. Many people as well as tourists visit the temple, especially during summer. The hillside and hilltop and greenery attract environmentalists to see the beauty of this hill station. Even many adventurers visit this place for trekking and rafting. The rivers Kapila and Kaveri flow through this hill station. Many different animal species, like Elephants, Leopards, Wild Dogs, One Horn Antelopes, Tigers, Sambar, Beers, Gawar are located in this region. While traveling to the temple, sometimes these animals are spotted by tourists in the middle of the road. Nearly 150 to 200 different bird species, like the Eagle and Drongo, are very abundant. B.R. Hills is very famous for the tribal group. Jenu kuruba, Betta kuruba, Hakik pikki, Koraga, and many other tribal groups are located in the different parts of the hill stations. The study area map made by using QGIS. To analyze the socio-economic development of these tribal groups, many methods have been used, like through Questioner and Observations. The study mainly focused on Socio-economic tribal Women's Status related to their Education, working conditions, health issues, economic condition and much other information collected, and SPSS and other simple methods used to make charts to get the results.